The role of music therapy in reducing post meal related anxiety for patients with anorexia nervosa. Issue 1 (December 2015) - Bibb, Jennifer; Castle, David; Newton, Richard
Abstract Background It is well known that mealtime is anxiety provoking for patients with Anorexia Nervosa. However, there is little research into effective interventions for reducing meal related anxiety in an inpatient setting. Methods This study compared the levels of distress and anxiety of patients with Anorexia Nervosa pre and post music therapy, in comparison to standard post meal support therapy. Data was collected using the Subjective Units of Distress (SUDS) scale which was administered pre and post each condition. Results A total of 89 intervention and 84 control sessions were recorded. Results from an unpaired t-test analysis indicated statistically significant differences between the music therapy and supported meal conditions. Conclusions Results indicated that participation in music therapy significantly decreases post meal related anxiety and distress in comparison to standard post meal support therapy. This research provides support for the use of music therapy in this setting as an effective clinical intervention in reducing meal related anxiety.